Temperature control of pseudo noise generator based optical transmitter using airflow and heat sink profile at high speed transceiver logic IO standard - Das, Bhagwan (Journal of Automation and Control Engineering, 2016)
Junction temperature is the final temperature of any device, after that device became dead. In this paper, junction temperature of target device i.e. Pseudo Noise sequence random generator based optical transmitter is controlled using heat sink profile and airflow. Heat sink and airflow are the cooling techniques for thermal efficient design on FPGA. We operated target device at high speed transceiver logic (HSTL) on FPGA at 1, 10,100 and 1000 (GHz) operating frequency. Each IO standard is examined with two airflow values (250 MFL and 500MFL) and Heat sink values (Low profile, Medium profile and high profile). For HSTL_I the reduction in junction temperature is (4%, 5%, 16% and 20%), HSTL_III (2%, 4%, 40%, and 67%), HSTL_I_18 (2%, 15%, 59%, and 68%), HSTL_III_18 (2.4%, 19%, 62%, and 74%) is recorded at respective frequencies. Significant reduction of 74% in junction temperature is observed at 1000GHz using HSTL_III_18. We conclude that for frequencies above 10GHz the heat sink profile and air flow significantly reduces the junction temperature using HSTL_III_18. This design makes the target device, energy efficient, system will be integrated with other optical components to make optical communication system green. Xilinx ISE14.7.1.2 design tool is used to perform the experiment.